THE PROBLEM OF DIALOGUE IN CONTEXT GLOBAL PROCESSES OF MODERNITY - Natalia Kovalchuk; Liudmyla Ovsiankina ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The article analyzes the global multipolar processes, to which representatives of all cultures of the world are involved today. There is an opinion that only intercultural dialogue in the near future should help to create a world solidary society, truly free and fair for all peoples, nations and countries, and not only for the "golden billion". In this context, the main task of the dialogue is to reconcile the representatives of different cultures and coordinate their efforts in joint activities to resolve political, environmental, socio-economic and demographic problems, to help all civilizations achieve social stability and socioeconomic growth. Special attention is paid to the analysis of S. Huntington's ideas about the confrontation that exists in intercultural communication between the West and other countries, as well as the determining factors of cultural identity (blood and faith, language, religion and family). People associate with those with whom they are in common and seek those with whom they are different. The article also analyzes the method of archetypes (proposed by S. Krymsky) as a mechanism for resolving conflicts arising in the intercultural communication of various ethnic groups. Its essence boils down to the fact that in ethnic conflicts that relate to the archetypal level of mentality of a certain people, representatives of different cultures should be bred. Ethnic groups, historically already have a common positive experience (in solving economic and political problems), it is much easier to understand each other and resolve any future conflicts on the way of integration.